Complications of appendicular fracture repair in cats and small dogs using locking compression plates - Vallefuoco, Rosario; Le Pommellet, Helene; Savin, Audrey; Decambron, Adeline; Manassero, Mathieu; Viateau, Véronique; Gauthier, Olivier; Fayolle, Pascal (Veterinary and Comparative Orthopaedics and Traumatology, 2016)
Objective: Our objectives were: 1) to review the complications associated with stabilization of appendicular fractures in cats and small dogs using locking compression plates (LCP), and 2) to identify factors that could influence fixation construct stability.Study design: Retrospective clinical study.Materials and methods: Medical and radiographic records of cats and small dogs with appendicular fractures treated with LCP were reviewed. Only cases with adequate follow-up to document clinical union and cases for which complications appeared before the clinical union were included. Complications were classified as implant-related complications or other complications. Cases with implant-related complications were compared to cases with non-implant-related complications for differences in signalment (species, age, body weight, multiple fractures), fracture location and type (fractured bone, fracture localization, closed or open fracture), reduction method (open reduction and internal fixation [ORIF] or minimally invasive plate osteosynthesis [MIPO]) and fixation evaluations (implant size, platebridging ratio, plate span ratio, working length, plate screw density, number of screws and cortices engaged per plate and per main fragment, ratio between screw and bone diameter at the narrowest aspect of the bone, and presence of ancillary fixation).Results: Seventy-five fractures from 63 cats (64 fractures) and 10 dogs (11 fractures) met the inclusion criteria. Eight humeral, 13 radio-ulnar, 26 femoral, and 28 tibio-fibular fractures were treated. Primary repair of the fracture was performed using 2.0 mm and 2.4 mm LCP in 22 and 53 fractures, respectively. Overall and implant-related complications were encountered in 13 and seven of 75 fractures, respectively. Fixation failure was not significantly associated with any aforementioned factor considered in this study, and in particular, there was no significant difference in the occurrence of fixation failure between fractures stabilized with two, or more than two, bicortical locking screws per main fragment.Clinical significance: 2.0 mm and 2.4 mm LCP were used to manage appendicular fractures in cats and small dogs. The overall complication and fixation failure rate were comparable to those reported in previous studies in which various locking plate systems were used.Online Supplementary Material for this article is available at: http://dx.doi.org/10.3415/VCOT-14-09-0146
Keywords: Dog; cat; fracture; locking compression plate; LCP